High body temperature detection solution through touchless machine for health monitoring - Swami, Siddharth; Mohan Joshi, Lalit; Ismail Iqbal, Mohammed; Sharma, Meera; Jeet Rawat, Amar; Dev Sharma, Sameer; Singh, Rajesh (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
The demand for reliable health monitoring systems has surged in today's health-conscious society. Body temperature monitoring is crucial for preserving health and preventing infectious disease outbreaks. In this study an Arduino uno hardware board with a touchless temperature sensor is proposed to detect elevated body temperature, indicating fever and early signs of illness. The system prioritizes real-time health surveillance, accessibility, and usability, blending seamlessly with normal life. Arduino's versatility allows the system to function covertly, uphold privacy and autonomy, and foster wellbeing. The goal is to highlight the system's ability to function covertly, uphold privacy and autonomy, and foster wellbeing. This technology exemplifies the synergy between personal wellness and contemporary technologies, offering a useful and adaptable fever detection solution for various contexts, including homes and public areas.